2019
DOI: 10.1182/blood-2018-08-872465
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of PI3Kα/δ is synergistic with BCL-2 blockade in genetically defined subtypes of DLBCL

Abstract: Inhibition of the B-cell receptor (BCR) signaling pathway is a promising treatment strategy in multiple B-cell malignancies. However, the role of BCR blockade in diffuse large B-cell lymphoma (DLBCL) remains undefined. We recently characterized primary DLBCL subsets with distinct genetic bases for perturbed BCR/phosphoinositide 3-kinase (PI3K) signaling and dysregulated B-cell lymphoma 2 (BCL-2) expression. Herein, we explore the activity of PI3K inhibitors and BCL-2 blockade in a panel of functionally and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 33 publications
8
73
0
3
Order By: Relevance
“…These clinical data reflect previous preclinical in vitro and in vivo studies that have suggested stronger activity of PI3K-α/-δ inhibition in ABC DLBCL compared with GCB DLBCL models [13][14][15]17]. The results are generally consistent with these findings, with copanlisib demonstrating a numerically higher response rate in ABC DLBCL compared with GCB DLBCL patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These clinical data reflect previous preclinical in vitro and in vivo studies that have suggested stronger activity of PI3K-α/-δ inhibition in ABC DLBCL compared with GCB DLBCL models [13][14][15]17]. The results are generally consistent with these findings, with copanlisib demonstrating a numerically higher response rate in ABC DLBCL compared with GCB DLBCL patients.…”
Section: Discussionsupporting
confidence: 87%
“…Copanlisib showed an acceptable safety profile, with the most common toxicities of hypertension and hyperglycemia being transient and manageable. To our knowledge, this is the largest phase II study on the use of a PI3K inhibitor in patients with DLBCL; therefore, further exploration of copanlisib in combination with other targeted therapies (e.g., a Bruton's tyrosine kinase inhibitor [14] or a BCL2 antagonist [15]) or in molecularly defined subgroups of DLBCL is warranted. In addition, a phase II study evaluating copanlisib in combination with rituximab-CHOP chemotherapy in previously untreated patients with DLBCL will be initiated in 2020 (EudraCT 2018-003560-31).…”
mentioning
confidence: 99%
“…Since activation of PI3K has been shown to limit the efficacy of venetoclax (21,22), we investigated whether the PI3K inhibitor idelalisib also synergized with venetoclax in inducing apoptosis in CLL cells. Indeed, in combination with the PI3K inhibitor, venetoclax-induced apoptosis was enhanced ( Fig.…”
Section: Stromal Pkc- Is Essential For Erk-activation and Bcl-x L Stmentioning
confidence: 99%
“…According to bioinformatics analysis, we found that hsa_circ_0072387 has similar miRNA-binding elements to that of hsa-miR-129-3p, hsa-miR-141-3p, and hsa-miR-29-3p. (Bojarczuk et al, 2018;Fahrioglu, Dodurga, Elmas, & Secme, 2016;Guestini et al, 2018). All these bioinformatics analyses indicated that hsa_ circ_0072387 is closely related to malignant tumors.…”
Section: Discussionmentioning
confidence: 89%
“…We further discovered that hsa_circ_0072387‐miR‐29‐3p/miR‐141‐3p‐MMP2/BCL2/PTEN pathways may play important roles in OSCC progression. Previous studies have reported that MMP2/BCL2/PTEN is activated in many cancers (Bojarczuk et al, ; Fahrioglu, Dodurga, Elmas, & Secme, ; Guestini et al, ). All these bioinformatics analyses indicated that hsa_circ_0072387 is closely related to malignant tumors.…”
Section: Discussionmentioning
confidence: 96%